NILAI TAMBAH PENGOLAHAN KELAPA MENJADI VCO DENGAN METODE BIASA DAN FERMENTASI - TIYAS MURTININGSIH (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2022)
Pure coconut oil or Virgin Coconut Oil (VCO) is a modification of the process of making coconut oil so that it produces products with low water content and free fatty acid levels, clear in color, smells good, and has a long shelf life of 12 months. The manufacture of virgin coconut oil has many advantages, namely it does not require expensive costs because the raw materials are easy to obtain at low prices, the processing is simple and not too complicated, while the use of energy is minimal because it does not use raw materials so that the chemical and nutritional content is maintained, especially acid. fat in oil. When compared with cooking oil (copra coconut oil), virgin coconut oil has better quality, copra coconut oil will be brownish yellow in color, odorless and easily rancid so that its shelf life does not last long (less than two months). From an economic point of view, virgin coconut oil (VCO) has a higher selling price than copra coconut oil, so studies on making VCO need to be developed.The process of making VCO (Virgin Coconut Oil) can be done using the usual method and the simple fermentation method.The advantage of making VCO (Virgin Coconut Oil) in Tugu Harum Village, Belitang Madang Raya, East OKU with the usual method is 0.019/month while the fermentation method is 0.020/month which means that it is financially feasible more than the current interest rate of 0.005 /Month.The added value obtained from the business of making VCO (Virgin Coconut Oil) with the usual method is Rp. 69,570/Kg While the fermentation method is Rp. 69,596.Keywords: coconut oil, value added, VOC